+0  
 
+2
766
2
avatar+598 

The value
\(\left(\frac{1+\sqrt 3}{2\sqrt 2}+\frac{\sqrt 3-1}{2\sqrt 2}i\right)^{72}\)
is a positive real number. What real number is it?

michaelcai  Dec 14, 2017

Best Answer 

 #2
avatar+89715 
+1

 

We can write

 

[   (1 + sqrt (3)   +  sqrt (3)i  - 1i  ] ^72  / sqrt (8)^72  =

 

[  ( 1 - i)   +  (1 + i) sqrt(3) ] ^72  / sqrt (8) ^72  =

 

[ [ (1 - i)  + (1 + i)sqrt(3) ]^2 ] ^36 / [sqrt (8)^2]^36 =

 

[ [ (1 - i)  + (1 + i)sqrt(3)]^2 / sqrt (8)^2 ] ^36

 

Forget  about  the exponent of 36  for a second and look at this

 

[ (1 - i)   +  (1 + i) sqrt (3) ] ^2 / [sqrt (8)]^2  =

 

[ (1 - i)(1 - i)   +  2 (1 - i) (1 + i)sqrt (3)  +  (1 + i)(1 + i) *3 ]/8   =

 

[  - 2i  + 2 ( 2)sqrt (3)  + 2i * 3 ]/ 8    =

 

[ 4i + 4 sqrt (3) ]  =   [  4  (  i  +  sqrt (3) ) ]  / 8   =

 

(1/2)  [ sqrt (3)  + i ]

 

So.......we have

 

[ (1/2)^36]  *  [ sqrt (3)  + i ]^36    =   A

 

Looking at  the red part we can write this as

 

(2)^36  ( cos [36 (pi/6)]  + i sin [ 36 (pi/6) ] )  =

 

(2)^36  (  cos [ 6pi ]  +  i sin [6pi] )  =

 

(2)^36  [  1  +  0i ]  =

 

(2)^36

 

So  A   becomes

 

[ (1/2)^36 ] * 2^36  =  [ 2 / 2 ] ^36  =  1^36  =

 

1

 

 

cool cool cool

CPhill  Dec 15, 2017
edited by CPhill  Dec 15, 2017
 #1
avatar
0

((1/2 + i/2) (sqrt(3) - i))/sqrt(2)=
Divide: 1 / 2 = 0.5
Divide: i / 2 = 0.5i
Square root: sqrt(3) = √ 3 = 1.7320508
Multiple: (0.5+0.5i) * (1.7320508-i) = 0.866025403784-0.5i+0.866025403784i+0.5 = 1.3660254+0.3660254i
alternative steps
0.7071068 × ei 45° × 2 × ei (-30°) = 0.707106781187 × 2 × ei (45°+(-30°)) = 1.4142136 × ei 15° = 1.3660254+0.3660254i
Square root: sqrt(2) = √ 2 = 1.4142136
Divide: (1.3660254+0.3660254i) / 1.4142136 = 0.9659258+0.258819i =(-1)^(1/12)
(-1)^(1/12)*72 =(-1)^6 =1

Guest Dec 14, 2017
 #2
avatar+89715 
+1
Best Answer

 

We can write

 

[   (1 + sqrt (3)   +  sqrt (3)i  - 1i  ] ^72  / sqrt (8)^72  =

 

[  ( 1 - i)   +  (1 + i) sqrt(3) ] ^72  / sqrt (8) ^72  =

 

[ [ (1 - i)  + (1 + i)sqrt(3) ]^2 ] ^36 / [sqrt (8)^2]^36 =

 

[ [ (1 - i)  + (1 + i)sqrt(3)]^2 / sqrt (8)^2 ] ^36

 

Forget  about  the exponent of 36  for a second and look at this

 

[ (1 - i)   +  (1 + i) sqrt (3) ] ^2 / [sqrt (8)]^2  =

 

[ (1 - i)(1 - i)   +  2 (1 - i) (1 + i)sqrt (3)  +  (1 + i)(1 + i) *3 ]/8   =

 

[  - 2i  + 2 ( 2)sqrt (3)  + 2i * 3 ]/ 8    =

 

[ 4i + 4 sqrt (3) ]  =   [  4  (  i  +  sqrt (3) ) ]  / 8   =

 

(1/2)  [ sqrt (3)  + i ]

 

So.......we have

 

[ (1/2)^36]  *  [ sqrt (3)  + i ]^36    =   A

 

Looking at  the red part we can write this as

 

(2)^36  ( cos [36 (pi/6)]  + i sin [ 36 (pi/6) ] )  =

 

(2)^36  (  cos [ 6pi ]  +  i sin [6pi] )  =

 

(2)^36  [  1  +  0i ]  =

 

(2)^36

 

So  A   becomes

 

[ (1/2)^36 ] * 2^36  =  [ 2 / 2 ] ^36  =  1^36  =

 

1

 

 

cool cool cool

CPhill  Dec 15, 2017
edited by CPhill  Dec 15, 2017

30 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.